THE INFLUENCE OF INCENTIVES AND SUPERVISION ON EMPLOYEE PRODUCTIVITY AT PT. PERKEBUNAN NUSANTARA VII BUSINESS UNIT PEMATANG KIWAH, NATAR SOUTH LAMPUNG REGENCY - Hazairin Habe; Nuzleha Nuzleha; Indriyani Indriyani; Ahiruddin Ahiruddin; Fahrizi Fahrizi; Yuliana Yamin (University of Sang Bumi Ruwa Jurai, 2018)
The object of this research is PT. Perkebunan Nusantara VII Kiwah Business Unit is located at Jalan Raya No. 71. A. Tanjungrejo village, Natar sub-district, South Lampung regency. Engaged in agribusiness and crumb rubber agroindustry qualified Standard Indonesian Rubber (SIR) for domestic and International market. Problems faced by this company is the discipline and awareness of achievement is still low, the supervision function has not been done properly, so that employee productivity is not optimal as planned. The purpose of this research is; (1) To know the effect of incentives on employee productivity at PT. Perkebunan Nusantara VII Business Unit Pematang Kiwah Natar South Lampung Regency, (2) To know the effect of supervision on employee productivity (3) To know the effect of incentives and supervision on employee productivity. The number of samples is 70 respondents. The result of data analysis using multiple linear regression formula is Y = 5,516 + 0,714 X1 + 0,722 X2 + e. Test Result F significant level 95% is F count 24,47 lebih dari F Table 3.15. Result of t test of significant level 95% is t count 6,224 lebih dari t Table 1,667. Thus incentives and supervision significantly affect the productivity of employees at PT. Perkebunan Nusantara VII Business Unit Pematang Kiwah Natar South Lampung Regency.